Kreativitas terhadap Minat Berwirausaha yang di Mediasi oleh Hasrat Berwirausaha pada Mahasiswa Kota Bandung - Hadya Zarifa; Jurry Hatammimi (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the relationship between creativity and interest in entrepreneurship, with the desire for entrepreneurship as a mediator, among Bandung City students. A quantitative approach was used with a purposive sampling technique. A total of 100 Bandung City students were respondents in this research. Data analysis was carried out using Structural Equation Modeling - Partial Least Squares (SEM-PLS), including outer model testing, inner model testing, and hypothesis testing. The research results show that creativity has a significant influence on entrepreneurial interest and entrepreneurial desire. In addition, it was found that the desire for entrepreneurship acts as a mediator between creativity and interest in entrepreneurship among Bandung City students. The conclusion is that the findings of this research can provide important insights for efforts to increase interest in entrepreneurship in society, especially among students. Keywords: Entrepreneurial Desire, Creativity, Entrepreneurial Interest